Preferred contents in Physical Education lessons - positively evaluated means for the achievement of a higher intensity of physical activity by girls [Oblíbená náplň vyučovacích jednotek tělesné výchovy - dívkami pozitivně hodnocený prostředek k dosahování vyšší intenzity pohybové aktivity] - Jana Vašíčková; Karel Frömel; Dagmar Sigmundová; Erik Sigmund (Palacky University, 2010)
BACKGROUND: Physical Education (PE) has been one of the key determinants in an education towards a physically active and healthy lifestyle. The role of PE is to form positive attitudes in children towards regular physical activity (PA) and show them the broad scale of types and intensities of PA and ways of teaching them. OBJECTIVE: The aim of this study is to examine relationships and identify determinants in the evaluation of PE lessons differing in content and PA intensity in girls. METHODS: To estimate the relationships between PA intensity in PE lessons and their evaluation, data on 2,213 girls aged 13-17 monitored in 205 PE lessons with different contents (aerobics n = 35, athletics n = 30, sport gymnastics n = 33, sport games n = 61 and dance n = 46) between 1997-2003 were used. PA intensity was monitored using the Caltrac (METs/45min.) accelerometer. To evaluate PE lessons, the standardized Assessment of Physical Education Lessons Questionnaire was applied (% of positive answers in the emotional, social, relationships, and health dimensions). RESULTS: In cases of preferred PA activities in girls (dance, aerobics, sport games), a higher PA intensity was reflected positively in the evaluation of PE lessons. In activities not preferred by girls (athletics and sport gymnastics), a higher PA intensity was reflected negatively in PE lesson evaluation. CONCLUSIONS: PE lessons with preferred contents such as dance, aerobics and sport games in girls are appropriate situations in which to carry out PA with a higher intensity. The employment of games or game - like lesson guidance can make PE lessons with less favoured content more attractive. [VÝCHODISKA: Školní tělesná výchova (TV) je v kontextu výchovy k pohybově aktivnímu a zdravému životnímu stylu jednou z klíčových determinant. Školní TV má dlouhodobě možnost formovat pozitivní postoje dětí k pravidelné pohybové aktivitě (PA) a realizovat ji v pestré škále jejích druhů, intenzit a didaktických forem. CÍLE: Cílem této studie je prezentovat vztahy a formulovat determinanty při hodnocení obsahově různých vyučovacích jednotek TV vzhledem k intenzitě PA děvčat. METODIKA: Ke zjišťování vztahů mezi intenzitou PA ve vyučovacích jednotkách TV a jejich hodnocením byla použita data od 2 213 děvčat ve věku 13–17 let monitorovaných ve 205 obsahově různých vyučovacích jednotkách TV (aerobik n = 35, atletika n = 30, sportovní gymnastika n = 33, sportovní hry n = 61 a tanec n = 46) v letech 1997–2003. Intenzita PA byla zjišťována akcelerometrem Caltrac (METs/45min.). K hodnocení vyučovacích jednotek TV byl použit standardizovaný Dotazník k diagnostice vyučovací jednotky TV (% kladných odpovědí v dimenzi emotivní, sociální, vztahové a zdravotní). VÝSLEDKY: U oblíbeného obsahu vyučovacích jed notek TV dívek (tanec, aerobik a sportovní hry) se vyšší intenzita PA projevila pozitivně v jejich hodnocení vyučovacích jednotek. U méně oblíbeného obsahu vyučovacích jednotek TV dívek (atletika a sportovní gymnastika) se vyšší intenzita PA projevuje negativně v jejich hodnocení vyučovacích jednotek. ZÁVĚRY: Vyučovací jednotky TV s oblíbeným obsahem (tanec, aerobik a sportovní hry) jsou pro děvčata vhodnými prostředky pro realizaci PA s vyšším tělesným zatížením. Zařazení pohybových her či herní forma vedení může zatraktivnit vyučovací jednotky TV s méně oblíbeným obsahem.]